Highlights of western civilization a Great courses anthology - Teaching Company (Chantilly, VA : Teaching Co., 2003)
Presents an anthology of lectures from courses on western civilization, taught by various noted professors.
Pt. VI. Modern times. Einstein to the rescue / Wolfson ; Robert Frost and the spirit of New England / Weinstein ; The rite of spring / Greenberg ; The war to end all wars, the experience of the trenches / Childers ; Ghandi's use of power / Dalton ; The grapes of wrath, American saga / Weinstein ; Rallying the nation / Fears ; Eisenhower and Operation Overlord / Childers ; John F. Kennedy, his final challenges / Lichtman ; The civil rights movement / Allitt ; The greatest success story in physics / Pollock ; Mikhail Gorbachev, Perestroika and Glasnost / Steinberg.
Teaching Co.: 8801--8806.
In six containers (22 cm.).
Keywords: Civilization, Western